PEMAHAMAN SISWA TENTANG MATERI AKHLAK TERPUJI PADA MATA PELAJARAN PAI HUBUNGANNYA DENGAN MOTIVASI BELAJAR PAI: Penelitian di kelas XI SMA Negeri 1 Rengasdengklok - Fadhil Santosa; Imam Tazali; Ellya Verawati; Wawan Ridwan; Amar Ma'ruf (STAI Pelabuhan Ratu, 2022)
Theoretically a good understanding will give high motivation to students. However, in real terms their motivation is low. This can be seen from some students in learning Islamic religious education are less enthusiastic about doing homework on the grounds that there are too many tasks, and are more concerned with other subjects, even though the material and understanding have been conveyed by the teacher council. The purpose of this study is to find out: 1) The understanding of class XI students of SMA Negeri 1 Rengasdengklok about commendable morals subpokok material of hard work, perseverance, tenacity, and meticulousness (X); 2) Motivation to learn PAI Class XI SMA Negeri 1 Rengasdengklok (Y); 3) The relationship between students' understanding of the sub-topic material of working hard, diligently tenaciously and meticulously with the motivation to learn PAI class XI SMA Negeri 1 Rengasdengklok. This research uses a descriptive method and for data collection through tests, questionnaires, interviews, observations, and literature studies. The results showed that students' understanding of moral material was commendable to the qualifications, 2. The reality of student learning motivation in the field of PAI includes high qualifications, 3. There is a positive relationship between students' understanding of commendable moral material in PAI subjects in relation to pai learning motivation, this is aimed at through the regression equation model Y = 49.25 + 0.11 X with a correlation coefficient of 0.51. The influence between the variable X on Y is 56% and there are other factors that affect the variable X againstY 44%.